Analisis Bangkitan Pergerakan Penduduk Berdasarkan Karakteristik Rumah Tangga di Kelurahan Morokrembangan Kota Surabaya - Revi Ayu Amelia; Theresia Maria C.A; Ratih Sekartadji; Kurnia Hadi Putra (Universitas Batanghari Jambi, 2026)
The ongoing population growth leads to high levels of community activity and mobility, especially in densely populated urban areas. Morokrembangan Village in Surabaya City is an area with significant traffic, supported by dense settlements and strategic access via Jalan Gresik, a connecting route between Surabaya and Gresik. To date, no study has specifically identified the magnitude of population activity by household characteristics in Morokrembangan Village, nor its relationship to population movement patterns supporting daily activities. Therefore, this study aims to analyze the characteristics and population movements based on household conditions. The method used is quantitative with probability sampling and simple random sampling techniques. Data analysis was carried out using validity and reliability, correlation, multiple linear regression, coefficient of determination, F and t tests, and SPSS Statistics 26. The results showed that the number of family members, trip purpose, and trip destination significantly influence population movement. Travel activities are dominated by work purposes, with the highest travel time in the morning, and the majority of movements occur in the North Surabaya area. Regression results indicate that the number of family members, trip purpose, and trip destination have a positive direction of influence on daily household trips, with regression coefficients of 0.511, 0.857, and 0.139, respectively. These findings can inform more effective and sustainable transportation planning and infrastructure development in the region.